Penerapan Teknik Bercerita menggunakan Media Boneka untuk Meningkatkan Minat Membaca AUD - Putri Kesawan; Junita Ningsih; Ali Masran (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Applying storytelling techniques using puppet media is an interesting method for increasing interest in reading in young children. This technique uses dolls as a visual medium that can attract children's attention, thus making the storytelling process more interactive and fun. Dolls, which act as characters in the story, are able to make the story more alive and make it easier for children to understand the message they want to convey. Apart from that, this technique encourages children to participate more actively, both in listening to stories and in responding to the stories being told, which in turn increases their interest in books and reading activities.The use of puppet media in telling stories can enrich children's learning experiences, because it not only develops listening and speaking skills, but also stimulates children's imagination, introduces new vocabulary, and forms a more creative way of thinking. With a more enjoyable atmosphere, children become more interested in reading books that contain similar stories, which helps strengthen their relationship with the world of literacy. Therefore, storytelling techniques using puppet media are an effective approach to introduce literacy from an early age, increase children's interest in reading, and develop their language skills.